Influence of the superplasticizing additive in concrete with lateritic aggregate: Influence of the superplasticizing additive in concrete with lateritic aggregate - Suárez Ferrufino, Andrea (2022)
Due to the scarcity and high transportation costs of stone aggregates in the east and northeast of Bolivia, different alternatives have been sought for their partial or complete replacement in the construction industry and, specifically, to produce concrete. The objective of this research is to evaluate the workability, compressive strength, and ultrasonic pulse velocity (UPV) of concrete produced entirely with coarse lateritic aggregates and a commercial superplasticizer additive. Using the IPT/EPUSP method, concrete with coarse lateritic aggregate was dosed for 30 MPa (design compressive strength). Five different percentages of additive (by weight of cement) were considered: 0% (reference), 0.6, 0.8, 1 and 1.2%. Although the superplasticizer additive improves workability at higher percentages, the mixtures with 0.6, 0.8 and 1% presented higher compressive strength and VPU, when compared to the reference (0%). 1.2% of additive presented the lowest values ​​of compressive strength and VPU. The use of additives, in this case superplasticizer, is beneficial for the workability and compressive strength of lateritic concrete, but the most appropriate content for its use must be defined.